From Alkanes to Carboxylic Acids: Terminal Oxygenation by a Fungal Peroxygenase. Issue 40 (30th August 2016) - Olmedo, Andrés; Aranda, Carmen; del Río, José C.; Kiebist, Jan; Scheibner, Katrin; Martínez, Angel T.; Gutiérrez, Ana
Abstract: A new heme–thiolate peroxidase catalyzes the hydroxylation of n ‐alkanes at the terminal position—a challenging reaction in organic chemistry—with H2 O2 as the only cosubstrate. Besides the primary product, 1‐dodecanol, the conversion of dodecane yielded dodecanoic, 12‐hydroxydodecanoic, and 1, 12‐dodecanedioic acids, as identified by GC–MS. Dodecanal could be detected only in trace amounts, and 1, 12‐dodecanediol was not observed, thus suggesting that dodecanoic acid is the branch point between mono‐ and diterminal hydroxylation. Simultaneously, oxygenation was observed at other hydrocarbon chain positions (preferentially C2 and C11). Similar results were observed in reactions of tetradecane. The pattern of products formed, together with data on the incorporation of 18 O from the cosubstrate H2 18 O2, demonstrate that the enzyme acts as a peroxygenase that is able to catalyze a cascade of mono‐ and diterminal oxidation reactions of long‐chain n ‐alkanes to give carboxylic acids. Abstract : A peroxygenase from the fungus Marasmius rotula was found to catalyze a cascade of mono‐ and diterminal oxygenation reactions of long‐chain n ‐alkanes to carboxylic acids in the presence of H2 O2 as the sole cosubstrate (see scheme). This peroxygenase type has great advantages for the mild activation of alkanes, with its self‐sufficient monooxygenase activity and its ability to hydroxylate the most unreactive terminal positions.